Review Artikel : Analisis Dan Formulasi Deodoran Berbahan Dasar Herbal Terhadap Kenyamanan Kulit - Nazila Khoerunnisa; Nadia Shinta Purnomo; Firdha Senja Maelaningsih (Pusat Riset dan Inovasi Nasional, 2024)
Body odour is a problem that interferes with daily life. The secretion of sweat glands and bacterial activity cause body odour. There are many ways to deal with the problem of body odour, including maintaining body hygiene and using skin care products such as deodorant and antiperspirant. The purpose of this review article is to determine the concentration levels of herbal-based active substances that are suitable for deodorant preparations and to determine their safety and comfort for the skin. This literature review article takes 4 main articles with 10 additional articles, spanning the last 10 years from 2013-2023. The results obtained from this review article show that all deodorant preparations have good formulation content. In spray-type deodorant preparations, the best formulation is deodorant with the active ingredient